Application of Piezoelectricity on Running Tracks: A Prototype for the Realization of Sustainable and Efficient Energy - Aldy Padmanegara Putra; Nurul Fahmi Arief Hakim; Erik Haritman; Silmi Ath Thahirah Al Azhima; Mariya Al Qibtiya (Green Publisher Indonesia, 2024)
Electrical energy has become a basic necessity today. As the population increases, the amount of electricity demand is also increasing. Therefore, many innovations are needed to meet these needs. One of the innovations in energy harvesting systems is the use of piezoelectricity. This research aims to create a piezoelectric-based running track prototype to produce environmentally friendly electrical energy. The arrangement of piezoelectric sensors used in this research is a parallel circuit. The research method used is the Research and Development method. The test results on the physical activities of walking, running, and jumping show that the prototype system that has been made has worked well and produces a fairly stable electric voltage even though it is still in a small amount. the difference in activity and body weight that presses the prototype produces different electric voltages. For walking activity, the prototype is able to produce a maximum voltage output of 0.83V, running activity has a maximum output of 5.83V and the maximum voltage output of jumping activity is 7.88V. The use of energy is done by storing the energy obtained from the piezoelectric in the battery, which can later be monitored directly by the voltage sensor, bluetooth module, HC-05, and RTC module the data will be sent to the cell phone so that the piezoelectric output voltage can be recorded and monitored. The electrical energy output generated by the piezoelectric is able to charge the battery and switch on the LED light at 2.5 V.